STUDY SITUATION AND THEMATIC APPROACH: RELATIONS, DISCUSSIONS END SIGNS (Revista Contexto & Educação, 2020)
The present work of qualitative searched through a bibliographical revision in National Meeting of Research in Science Education investigate the approximations and distances between the perspectives of the Thematic Approach and the Study Situation, and there by, to discuss their relations with the school curriculum. The time-cut of there vision occurred in the period from 1997 to 2015. The analysis of the data was basedon the Discursive Textual Analysis and as main results of the research, it should be noted that the Thematic Approach is based on Freirean Liberating Education and the Study Situation in Vygotsky's frame of reference, but both perspectives are identified as proposals for curricular reorganization guided by themes in order to contemplate na interdisciplinary and contextualized teaching.